Partisipasi Politik Perempuan pada Partai Keadilan Sejahtera Kota Medan - Susi Susanti; Adelita Lubis (Universitas Medan Area, 2015)
Participation is one of the fundamental aspects in the course of the Democratic administration. In this study, the Women's Political Participation in the Prosperous Justice Party (PKS) is quite high. It can be seen from their involvement in the management of the party. But the discussion of women's issues in politics and always have ups and downs of a women's political participation in the City field. From the results of this research note that women's political involvement or participation in the MCC is quite high. It is caused by several factors, including the most dominant cultural factors, and factors are less known women from the MCC. To keep pace with the need to understand the role and the authority held and used for the progress of women. The problems described in this study is the low level of political participation of women in Medan City Council 2009-2014 period, as pemeenuhan quota of 30% women candidates who have not really seriously implemented by parties that exist in Indonesia.